2016
DOI: 10.3892/etm.2016.3633
|View full text |Cite
|
Sign up to set email alerts
|

Part of plasmapheresis with plasma filtration adsorption combined with continuous hemodiafiltration in the treatment of severe acute liver failure

Abstract: The present study is a retrospective analysis of 11 cases with severe acute liver failure combined with multiple organ dysfunction syndrome (MODS) performed during the period June, 2012 to December, 2014. After part of plasmapheresis with plasma filtration adsorption combined with continuous hemodiafiltration treatment, good curative effects were obtained and the main clinical symptoms and biochemical index were significantly improved. Following treatment, 8 of the 11 patients survived at a survival rate of 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Previous reports have suggested that patients with hepatic coma have worse clinical outcomes. [ 14 15 ] Hence, it may seem prudent to treat these patients aggressively. Extracorporeal therapy, other than hemodialysis, has been tried in such cases, with good results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that patients with hepatic coma have worse clinical outcomes. [ 14 15 ] Hence, it may seem prudent to treat these patients aggressively. Extracorporeal therapy, other than hemodialysis, has been tried in such cases, with good results.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it helps to maintain the biochemical and homeostatic balance in the body. By this method, the compensation of liver metabolism will lead to the necessary time for the patient's own liver regeneration to occur 3,8,9 . In recent years, it has been shown that PE is effective in the emergency treatment of liver failure [10][11][12][13] .…”
Section: Hyperbilirubinemiasmentioning
confidence: 99%
“…-Плазмосорбция и плазмофильтрация эффективно снижают уровень билирубина и других токсических метаболитов, образующихся на фоне механической желтухи и холестаза [112][113][114][115]. Уровень достоверности (доказательности) В. Уровень убедительности рекомендации IIa.…”
Section: заместительная печеночная терапияunclassified
“…Сочетание сеансов плазмосорбции с последующей непрерывной венозной гемодифильтрацией использовали у пациентов с острой ПечН M. Li и соавт. [114]. Исследование было нерандомизированным и включало всего лишь 11 пациентов.…”
Section: заместительная печеночная терапияunclassified